Copper-antimony-selenium thin film for all-solid-state thin film lithium ion battery and preparation method of copper-antimony-selenium thin film

CuSbSe2 thin films are prepared by mixing Cu powder, Sb powder and Se powder by mechanical ball milling, and combining vacuum evaporation and rapid thermal annealing technology, which solves the problems of complex process and high cost in the existing technology, and achieves the preparation of high-performance CuSbSe2 thin films. .

CN119340348AActive Publication Date: 2025-01-21HEBEI UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411453905.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The prior art has high cost and cumbersome process when preparing CuSbSe2 films, and the ion and electron transport characteristics of the films are insufficient, which affects the overall performance of the battery.

Method used

After mixing Cu powder, Sb powder and Se powder using mechanical ball milling, a CuSbSe2 amorphous film is deposited on the current collector through vacuum evaporation technology, and rapid thermal annealing is performed in an inert atmosphere to obtain a crystallized CuSbSe2 film.

Benefits of technology

The ion and electron transport characteristics of the CuSbSe2 film are improved, and the overall performance of the battery is improved. The process is simple, the cost is low, and it is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340348A_ABST
    Figure CN119340348A_ABST
Patent Text Reader

Abstract

The invention provides a copper-antimony-selenium thin film for an all-solid-state thin-film lithium ion battery and a preparation method, and belongs to the technical field of thin-film solid-state lithium ion batteries and manufacturing of the thin-film solid-state lithium ion batteries. The method comprises the following specific operation steps: firstly, preparing a CuSbSe2 precursor by using a mechanical ball milling method, carrying out vacuum calcination, then evaporating a layer of CuSbSe2 on a current collector by using a vacuum evaporation method, and finally, carrying out thermal annealing for 30-90 seconds at 300-600 DEG C by using a rapid annealing furnace to form the CuSbSe2 film. The process of first evaporating and then annealing can enhance the binding force of the thin film and the substrate, the purity of the thin film layer is improved, the preparation process is simple, and the cost is low. The CuSbSe2 negative electrode thin film has excellent charge-discharge specific capacity and cycling stability, has a wide development prospect in the field of solid-state thin film batteries, and is suitable for further popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state thin-film lithium-ion batteries and their manufacturing, and specifically relates to a copper antimony selenium (CuSbSe2) negative electrode film and a preparation method thereof. Background Art

[0002] All-solid-state thin-film lithium-ion batteries (ASSTFBs) are a key technology for achieving carbon neutrality goals and provide a clean energy storage solution to combat climate change. Their application in electric vehicles and energy storage systems has significant advantages, especially in terms of fast charging and low-temperature performance. With the miniaturization of microelectronic devices, the demand for compact and efficient power sources increases, and ASSTFBs have become an ideal choice with their high energy density and safety. ASSTFBs have broad development prospects and are expected to be widely used in fields such as smart devices, medical implants and wearable technologies.

[0003] Anode materials play a vital role in thin-film lithium-ion batteries. They not only directly affect the energy density and power density of the battery, but also determine the cycle stability and overall performance of the battery. The high specific surface area and good electronic conductivity of the negative electrode film help improve the charge and discharge efficiency of the battery, and its thin-film structure is conducive to improving the mechanical stability and thermal stability of the battery. In addition, the uniformity and consistency of the thin-film negative electrode are crucial to ensure the reliability of the battery under various working conditions. At present, common thin-film negative electrode materials include lithium titanate and silicon-based materials. Although lithium titanate negative electrode materials have the advantages of fast charge and discharge speed, high number of cycles and high safety, their specific capacity is relatively low. The theoretical specific capacity of silicon-based materials is as high as 4200 mAh / g, but during the charge and discharge process, silicon will undergo severe volume expansion, resulting in battery capacity attenuation and decreased Coulombic efficiency. To this end, the development of a negative electrode with high specific capacity and high stability is of great significance for the development of all-solid-state thin-film lithium-ion batteries that can adapt to harsh environments such as industry and military.

[0004] CuSbSe2 has a theoretical specific capacity of about 470 mAh / g and has excellent cycle performance, making it one of the candidates for negative electrode films of lithium-ion batteries. At present, the method for preparing CuSbSe2 thin films is mainly multi-step magnetron sputtering, which is costly, slow in deposition rate and complicated in process steps. Summary of the invention

[0005] In view of this, the present invention provides a CuSbSe2 thin film and a preparation method thereof; the CuSbSe2 thin film enhances the ion and electron transport properties of the CuSbSe2 thin film and improves the overall performance of the battery.

[0006] The present invention adopts the following technical solutions to achieve the above technical effects: A method for preparing an all-solid-state thin-film lithium-ion battery comprises the following steps: Step 1, preparing CuSbSe2 precursor material by mechanical ball milling; Step 2, placing the CuSbSe2 precursor material in a vacuum sintering furnace for calcining; Step 3, placing the current collector in a solution for ultrasonic cleaning, and then placing it in an oven for drying; Step 4, using the calcined CuSbSe2 precursor material as an evaporation source, and using vacuum evaporation technology to deposit a CuSbSe2 amorphous film on a current collector; Step 5: The CuSbSe2 amorphous thin film material is subjected to rapid thermal annealing in an inert atmosphere to obtain a crystallized CuSbSe2 thin film.

[0007] Furthermore, in step 1, the process parameters of mechanical ball milling are: rotation speed of 200-400 rpm; time of 6-12 hours.

[0008] Furthermore, in step 1, the raw materials for mechanical ball milling are Cu powder, Sb powder and Se powder, and the stoichiometric ratio thereof is Cu:Sb:Se=1:1:2.

[0009] Furthermore, in step 2, the process parameters of the vacuum sintering furnace are: the vacuum degree needs to reach 1×10 -3 ~5 Pa; calcination temperature is 200~500℃; time is 0.5~3 h.

[0010] Furthermore, in step 3, the current collector is a mixture of any one or more of steel sheet, steel foil, stainless steel sheet, copper sheet, copper foil, and foam copper; and the oven temperature is 45-55 °C.

[0011] Furthermore, in step 3, the current collector is washed with acetone, anhydrous ethanol and deionized water in sequence; the washing time is 15 to 30 minutes; Furthermore, the process parameters of the vacuum evaporation in step 4 are as follows: the vacuum degree needs to reach 2×10 -4 ~7×10 -4 Pa; the current collector temperature is room temperature 25°C; the distance between the evaporation source and the current collector is 7-12 cm; the current applied to the tungsten boat is 60-80A; the substrate tray rotation speed is 3-10 rpm; and the evaporation time is 15-30 min.

[0012] Furthermore, in step 5, the inert atmosphere is helium, neon, argon or krypton.

[0013] Furthermore, the temperature of the rapid thermal annealing in step 5 is 300-600° C., and the time is 30-90 s.

[0014] The CuSbSe2 negative electrode film was prepared by the above preparation method.

[0015] Compared with the prior art, the present invention proposes for the first time a method for preparing CuSbSe2 thin film by using a ball-milled mixed material of Cu powder, Sb powder and Se powder as an evaporation source and vacuum evaporation combined with rapid thermal annealing. The preparation method is simple and easy to implement and has the following advantages: ① The three raw materials are non-toxic or low-toxic, easy to obtain and low in cost; ②The ball milling method has a simple process, does not cause environmental pollution, and is highly safe.

[0016] ③ The vacuum-evaporated amorphous CuSbSe2 film has uniform thickness and compact structure, which is suitable for complex geometric shapes and fine structures; and the film deposition rate is fast, which improves production efficiency and reduces preparation costs. The evaporation process does not cause environmental pollution and is beneficial to environmental protection.

[0017] ④ Rapid thermal annealing technology can crystallize amorphous materials in a very short time, significantly reduce stress and defects in the film, and improve the crystal quality and charge transfer efficiency of the film; at the same time, it can also reduce the thermal budget, energy consumption and environmental impact. Therefore, the method proposed in the present invention provides an efficient, low-cost and excellent performance solution for the manufacture of CuSbSe2 negative electrode films for all-solid-state thin-film lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The schematic diagram of the structure of the vacuum evaporation equipment used in the preparation of CuSbSe2 thin film in the present invention.

[0019] Figure 2 This is the XRD diffraction pattern of the CuSbSe2 thin film prepared in Example 1 of the present invention.

[0020] Figure 3 This is a SEM image of the CuSbSe2 thin film prepared in Example 1 of the present invention.

[0021] Figure 4 This is the cyclic charge-discharge curve (0.5 C) of the CuSbSe2 film prepared in Example 1 of the present invention.

[0022] Figure 5 This is the cyclic charge-discharge curve (0.5 C) of the CuSbSe2 film prepared in Example 2 of the present invention.

[0023] Figure 6 This is the cyclic charge-discharge curve (0.5 C) of the CuSbSe2 film prepared in Example 3 of the present invention.

[0024] Figure 7This is the cyclic charge-discharge curve (0.5 C) of the CuSbSe2 powder prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1, a method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery Step 1, mix Cu powder, Sb powder and Se powder with a molar ratio of 1:1:2 and put them into a ball mill, add anhydrous ethanol as a process control agent, set the ball mill speed to 240 rpm, the time to 8 h, and place the ball mill in a 45°C drying oven after ball milling to obtain a CuSbSe2 precursor after drying.

[0027] Step 2: Place the precursor into a vacuum sintering furnace, set the calcination temperature to 400 °C, and the time to 1 h to obtain CuSbSe2 powder material.

[0028] Step 3: ultrasonically clean the stainless steel current collector, remove residual grease with acetone solution, remove residual acetone with anhydrous ethanol, and remove residual ethanol with deionized water, and then dry it in a drying oven at 45 °C for 12 hours to remove residual moisture.

[0029] Step 4: Use Figure 1 The high vacuum four-source evaporation coating machine shown in the figure is used for thin film evaporation. Open the vacuum evaporation equipment cavity, open the metal source baffle 5, take out the tray 3 and the tungsten boat 4, use sandpaper to polish the impurities on the tray 3 and the tungsten boat 4, and then wipe them clean with alcohol. Place the cleaned stainless steel collector on the tray 3, and place the CuSbSe2 powder evenly on the tungsten boat 4 to ensure that the powder is heated evenly during heating. Place the tray 3 on the rotating base 2 and fix it. Set the distance between the substrate and the evaporation source to 10 cm, the substrate tray speed to 5 rpm, close the metal source baffle 5, and close the cavity. The vacuum degree of the cavity is evacuated to 5×10 -4 Pa, turn on the tray rotation, open the metal source baffle 5, turn on the tungsten boat 4 control power, adjust the evaporation current to 80 A, and the evaporation time to 25 min.

[0030] Step 5: Place the stainless steel current collector with the evaporated film into a rapid annealing furnace and anneal it at 500 °C in an argon atmosphere for 30 seconds to obtain a CuSbSe2 film.

[0031] The CuSbSe2 film prepared in Example 1 was characterized by XRD, and the results are shown in Figure 2. All peaks of the negative electrode material can correspond to the standard spectrum, and the preferred orientation of the film growth is <020> , belonging to the Pnma(62) space group.

[0032] The CuSbSe2 film prepared in Example 1 was characterized by SEM, and the result is shown in Figure 3. The negative electrode material is in the shape of stacked nanorods.

[0033] The CuSbSe2 film prepared in Example 1 was subjected to a cyclic charge-discharge test at 0.5 C. The results are as follows: Figure 4 Its discharge capacity reaches 1294.35 mAh g -1 , the charging capacity reaches 1259.13 mAh g -1 The first coulombic efficiency is 97.28%, and the capacity retention rate after 200 cycles is 91.22%, indicating that this method can prepare CuSbSe2 negative electrode films with excellent electrochemical properties.

[0034] Example 2, a method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery Compared with Example 1, in the present embodiment, when preparing the CuSbSe2 thin film, during the rapid thermal annealing process, the annealing temperature is adjusted to 400° C. The remaining steps are the same as those in Example 1.

[0035] The CuSbSe2 negative electrode film prepared in Example 2 was subjected to a cyclic charge-discharge test at 0.5 C. The results are as follows: Figure 5 shown.

[0036] Example 3, a method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery Compared with Example 1, in the present embodiment, when preparing the CuSbSe2 thin film, during the rapid thermal annealing process, the annealing temperature is adjusted to 600° C. The remaining steps are the same as those in Example 1.

[0037] The CuSbSe2 negative electrode film prepared in Example 2 was subjected to a cyclic charge-discharge test at 0.5 C. The results are as follows: Figure 6 shown.

[0038] Cu, Sb, and Se powders with a stoichiometric ratio of 1:1:2 were ground in a mortar for 30 min, and the resulting mixture was then - 2 The quartz tube was sealed in a vacuum quartz tube at a pressure of 1.3 Pa. The quartz tube was then heated to 810 °C at a heating rate of 2 °C / min and kept isothermally for 150 h to obtain CuSbSe2 powder.

[0039] Figure 7 This is the cyclic charge-discharge curve of the CuSbSe2 powder negative electrode prepared in this comparative example 1 at a current density of 0.5 C.

[0040] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

[0041] and variants.

Claims

1. A method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery, characterized in that: A CuSbSe2 film is used as the negative electrode film. The film is prepared by the following method, which specifically includes the following steps: Step 1, preparing CuSbSe2 precursor material by mechanical ball milling; Step 2, placing the CuSbSe2 precursor material in a vacuum sintering furnace for calcining; Step 3, placing the current collector in a solution for ultrasonic cleaning, and then placing it in an oven for drying; Step 4, using the calcined CuSbSe2 precursor material as an evaporation source, and using vacuum evaporation technology to deposit a CuSbSe2 amorphous film on a current collector; Step 5: The CuSbSe2 amorphous thin film material is subjected to rapid thermal annealing in an inert atmosphere to obtain a crystallized CuSbSe2 negative electrode thin film.

2. The method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery according to claim 1, characterized in that: In the step 1, the process parameters of mechanical ball milling are: rotation speed of 200-400 rpm; time of 6-12 h.

3. The method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery according to claim 1, characterized in that: In the step 1, the raw materials for mechanical ball milling are Cu powder, Sb powder and Se powder, and the stoichiometric ratio thereof is Cu:Sb:Se=1:1:

2.

4. The method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery according to claim 1, characterized in that: In step 2, the process parameters of the vacuum sintering furnace are: the vacuum degree needs to reach 1×10 -3 ~5 Pa; calcination temperature is 200~500℃; time is 0.5~3 h.

5. The method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery according to claim 1, characterized in that: In step 3, the current collector is a mixture of any one or more of steel sheet, steel foil, stainless steel sheet, copper sheet, copper foil, and foam copper; and the oven temperature is 45-55 °C.

6. The method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery according to claim 1, characterized in that: In step 3, the current collector is cleaned by acetone, anhydrous ethanol and deionized water in sequence; the cleaning time is 15 to 30 minutes.

7. The method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery according to claim 1, characterized in that: The process parameters of the vacuum evaporation in step 4 are as follows: the vacuum degree should reach 2×10 -4 ~7×10 -4 Pa; the current collector temperature is room temperature 25℃; the distance between the evaporation source and the current collector is 7-12 cm; the current applied to the tungsten boat is 60-80 A; the substrate tray rotation speed is 3-10 rpm; and the evaporation time is 15-30 min.

8. The method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery according to claim 1, characterized in that: In step 5, the inert atmosphere is helium, neon, argon or krypton.

9. The method for preparing a copper antimony selenium thin film for an all-solid-state thin film lithium ion battery according to claim 1, characterized in that: The temperature of the rapid thermal annealing in step 5 is 300-600° C., and the time is 30-90 s.

10. A copper antimony selenium thin film for all-solid-state thin film lithium ion battery, characterized in that: A CuSbSe2 negative electrode thin film prepared by a preparation method for an all-solid-state thin-film lithium-ion battery as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Cathode of three-dimensional net wall-shaped all-solid-state lithium ion battery, preparation method, and battery

    CN108711608A

  • A 3D thin film negative electrode of all-solid-state thin film lithium ion battery and a preparation method thereof

    CN109167061A

  • Negative electrode-solid electrolyte subassembly, all-solid secondary battery, and method for preparing all-solid secondary battery

    CN116137318A

  • Manufacture of lithium negative electrode

    JP1991105854A

  • Surface modified solid-state electrolytes, processes for their preparation, and their use in electrochemical cells

    WO2024011318A1